Slimnastics Is Fun - Jones, MG Sholtis (Leisure Services Publications, 1976)
Keywords: Exercise; dept.rec; faculty_collection

Me Is How I Feel: Poems, - Crossen, Stacy Jo; Covell, Natalie Anne; De Larrea, Victoria (McCall Pub. Co, 1970)
Thirteen poems about such emotions as happiness, frustration, anger, pride, loneliness, love, and disappointment.
Keywords: dept.rec; faculty_collection

Relax and run - Myerson, Sandra H (Journal of Physical Education and Recreation, 1979)
Keywords: dept.rec

College Football and Social-Mobility - Case-Study of Notre-Dame Football Players - Sack, AL; Thiel, R (Sociology of Education, 1979)
Keywords: dept.rec

Locus of control among Dutch and American women softball players. - Finn, Joan A; Straub, William F (Research Quarterly. American Alliance for Health, Physical Education and Recreation, 1977)
Locus of control is a personality variable that manifests itself through an individual’s perception of the reinforcement he receives. This belief system is based on a continuum ranging from the perception that rewards are completely contingent upon one’s behavior to the belief that only luck, chance, or fate control one’s life. This construct has received considerable attention within the realm of psychology, but is conspicuous by its absence in sport and physical education literature. The purpose of this study was to compare the locus of control of highly skilled Dutch (N = 35) and American (N = 44) women softball players. The Rotter internal-external locus of control scale was utilized to determine internal-external orientations of the subjects. Data were analyzed by using ANOVA and product moment correlations. Statistically significant (.01 level) differences in locus of control were found. American women softball players were significantly more internally oriented than were their Dutch counterparts. © 1977 Taylor 8 Francis Group, LLC.
Keywords: Adolescent; Adult; Baseball; Comparative Study; Cross-Cultural Comparison; Female; Human; Male; Netherlands; Personality; Sports; United States; adolescent; adult; article; baseball; comparative study; cultural factor; dept.rec; female; human; male; personality; sport

Julian smith 1901–1975 - Donaldson, George W.; George, Jack F. (Journal of physical education and recreation, 1975)
Keywords: dept.rec

A report from the NFHPER board of directors - George, Jack (Journal of health,physical education and recreation, 1972)
Keywords: dept.rec

The masters program in physical education with a specialization in physical education-recreation for the handicapped - Bonis, Edith De (Journal of health,physical education and recreation, 1971)
Keywords: dept.rec